Evaluasi Kerusakan Jalan Berdasarkan Metode Surface Distress Index, Binamarga 1990, Serta Berbasis Software PKRMS - Maharani, Elvina; Hadi Putra, Kurnia (Jurnal Etnik: Ekonomi-Teknik, 2023)
Baturono – Lamongan road is a distrit road that connects the districs of Sukodadi, Made, Lamongan. The road is an alternative road which is the main accesss so that there is a large volume of vehicles passing throught the road. Therefore, resulting in road damage that can interfere with user comfort and safety. This research to determine the type of road handling in accordance with the condition of the road damage. This esearch was carried out by means of primary data surveys in the form of LHR and road damage surveys. The methods used are Bina Marga 1990, Surface Distress Index (SDI), and PKRMS Software. On the Baturono road section ound the types of damage holes, pathces, transverse cracks, longitudinal, ruts, and alligator cracks. By using the Bina Marga method the priority order value is 10 including type of routine maintenance. The SDI methode yielded 37,85 < 50 so that is included of routine maintenance. Meanwhile, software PKRMS output software obtained good results which included routine maintenance. The handling carried out refers to the practical manual of routine maintenance in the form of filling cracks, spreading sand, and closing crack.